Determinantes da estrutura de capital das empresas de edificações brasileiras na crise - Damascena, Daniele Santos (2018)
Starting in 2014, due to the uncertainties caused by political and economic instability, the Brazilian GDP began to show negative signs and to impact the entire economy. The performance of the building industry was one of the first to be compromised. The main objective of this research was to identify and analyze the factors determining the capital structure of the five largest companies in the building sector listed on the São Paulo Stock Exchange, from 2010 to 2017, considering the assumptions of three capital structure theories: Pecking Order, Agency and Trade off. The period studied was between the first quarter of 2010 and the first quarter of 2017, totaling 29 quarters for each company. The accounting data was extracted from the Economática database. First, a graphical analysis of the accounting and financial performance of these companies was carried out. Afterwards, panel data analysis was performed, considering indebtedness indices as dependent variables and the factors of profitability, tangibility, growth and liquidity as independent variables. The evident result was the observation of adherence to the precepts of the Pecking Order Theory for the variables of profitability and liquidity in the period prior to the political-economic crisis. During the Crisis, it was observed that the variables Growth and Tangibility were the most affected by the fact that they served as collateral in credit operations